Recovery of intercalated Li and synthesis of reduced graphene oxide from graphite of spent Li-ion battery for supercapacitor application - Uppin, Bhagyashree; Sankannavar, Rohini; Kangutkar, Raju S.; Manjanna, Jayappa; Kolekar, Sanjay; Nayaka, Girish P. (Inorganic Chemistry Communications, 2025)
Spent Li-ion batteries (LIBs) are accumulating rapidly across the world. Anode portion of spent LIBs is comprised of graphite with a significant amount of intercalated Li. Thus, it serves as an important secondary resource of Li. Therefore, this study is focused on the eco-friendly recovery of Li from anode graphite and the conversion of recovered graphite (RG) into reduced graphene oxide (rGO) for its application in supercapacitors. The spent graphite (SG) was dissolved in 0.5 M oxalic acid with a solid-liquid ratio of 50 g L- 1 at 70 degrees C for about 90 min. Under given condition, 100 % Li was extracted from graphite. The dissolved Li was successfully recovered as Li2CO3. Further, RG was used as a precursor for the synthesis of GO and then converted to rGO by reduction with gallic acid under microwave irradiation. As synthesized rGO was used as an electrode material for supercapacitor application. The rGO electrode exhibited highest specific capacitance of 1211 F g- 1 at a current density of 4 mA cm- 2. It showed energy density 168.2 W h kg- 1 and power density 1000 W kg- 1 with stability up to 2000 cycles (90 % retention). Further, asymmetric solid-state device (rGO//activated carbon) was fabricated with polyvinyl alcohol - H2SO4 as electrolyte. It exhibited high energy density of 94 W h kg- 1 at a power density of 1200 W kg- 1 and cycling stability up to 1500 cycles with 86.20 % capacity retention. Hence, rGO synthesized from spent LIB provides an excellent electrode material for construction of supercapacitor devices.
Keywords: Graphite anode; Lithium recovery; Recovered graphite; rGO synthesis; Spent Li-ion battery; supercapacitor

Enhanced photocatalytic hydrogen evolution in deionized/natural seawater and removal of organic pollutants using the heterostructure of CuO/Cu2O nanoparticles under visible light - Kangutkar, Raju S.; Walko, Priyanka; Nayaka, Girish Praveen; Nigam, Sandeep; Majumder, Chiranjib; Manjanna, Jayappa (Langmuir, 2026)
Water splitting for hydrogen production and reducing water pollution using solar light are part of the Sustainable Development Goals, which require highly active photocatalytic materials. The heterostructures have demonstrated remarkable photocatalytic advantages in visible light. Herein, we report microwave-assisted green synthesis of CuO/Cu2O nanoparticles using Tridax plant leaf extract. The synthesized nanoparticles were characterized by using PXRD, UV-DRS, Raman spectroscopy, XPS, PL, TRPL, FE-SEM, HR-TEM, BET, and photocurrent. The photocatalytic water splitting performance of CuO/Cu2O and CuO was measured under visible light (lambda >= 420 nm) irradiation using methanol as a sacrificial reagent in DI water and natural seawater. The H2 evolution rates in DI water for CuO/Cu2O and CuO are 2043.21 and 970.09 mu mol g-1 h-1 with apparent quantum efficiency (AQE) values of 5.60 and 2.66 %, respectively. In natural seawater, the H2 evolution rates are 2599.29 and 1370.54 mu mol g-1 h-1 with AQE values of 7.12 and 3.75 %, respectively. The rate of H2 evolution slightly increased in natural seawater. Also, the degradation of the methylene blue dye was examined here, and the efficiency of CuO/Cu2O was determined to be 97 % under natural sunlight. Electrocatalytic H2 evolution was also studied here by using linear sweep voltammetry. Tafel slope values for CuO/Cu2O and CuO are 153 and 250 mV dec-1, respectively. The lowest Tafel value of CuO/Cu2O indicates a faster rate of reaction, thereby producing easier charge separation and lowering the electron-hole recombination due to the presence of surface defects, smaller particle size, enhanced crystallinity, and the synergistic effect between Cu2O and CuO.